1994
DOI: 10.1111/j.1439-0264.1994.tb00479.x
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Observations of the Coronary Sinus in the Dog (Canis familiaris)

Abstract: The coronary sinus was investigated in 34 normal adult dogs, in order to verify its formation, tributaries, length and the valves, as well as the relationship of the venous walls to the epicardium and to the myocardium. The valve of the coronary sinus was observed in only 4 cases (1.7%). In 30 cases (98.3%) the ostium of the coronary sinus was lacking a valve. The valve of Vieussens double, was found at the level of the transition between the great cardiac vein and the coronary sinus, as well as others parieta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The CS is typically connected to the great cardiac vein (GCV), then to the anterior interventricular vein (AIV), followed by the posterior interventricular vein (PIV) which begins close to the apex of the heart and goes into the posterior interventricular groove and enters the CS close to the CS ostium [30]. The normal cardiac venous drainage has been described in the literature for pigs [31][32][33] and dogs [34][35][36], and to a lesser extent in the sheep [37].…”
Section: Introductionmentioning
confidence: 99%
“…The CS is typically connected to the great cardiac vein (GCV), then to the anterior interventricular vein (AIV), followed by the posterior interventricular vein (PIV) which begins close to the apex of the heart and goes into the posterior interventricular groove and enters the CS close to the CS ostium [30]. The normal cardiac venous drainage has been described in the literature for pigs [31][32][33] and dogs [34][35][36], and to a lesser extent in the sheep [37].…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations have shown that the great cardiac vein and the middle cardiac vein open into the coronary sinus, and the coronary sinus is the continuation of the great cardiac vein in dogs (Ghoshal, 1975; Esperenca et al, 1981; Nickel et al, 1981; Evans and Christensen, 1993; Piffer et al, 1994; Maric et al, 1996) and in cats (Ghoshal, 1975; Nickel et al, 1981; Aksoy et al, 2001). Observations in the present study support these findings.…”
Section: Discussionmentioning
confidence: 98%
“…Drainage of the heart is carried out by the great cardiac vein, the middle cardiac vein, the right cardiac veins and the smallest cardiac veins (Hegazi, 1958; Nickel et al, 1981; Yadm and Gad, 1992; Yadm, 1993; Aksoy et al, 2001). The great cardiac vein and the middle cardiac vein terminate at the coronary sinus which is constituted by the continuation of the great cardiac vein (Ghoshal, 1975; Esperenca et al, 1981; Nickel et al, 1981; Yadm and Gad, 1992; Piffer et al, 1994; Maric et al, 1996; Aksoy et al, 2001). The coronary sinus opens into the right atrium ventral to the opening of the caudal vena cava, and it has a semicircular valve (Crouch and Lackey, 1969; Field and Taylor, 1969; Getty, 1975; Ghoshal et al, 1981; Yadm, 1993; Aksoy et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are several studies [2,3,16,19] on the venous systems of the domestic carnivorous animals' hearts, there is only one study on the wild animals [18], which is built on the macroanatomical features of a tiger heart that died in a local ZOO. For the first time, with this study, the veins of the red fox heart were examined extensively.…”
Section: Discussionmentioning
confidence: 99%